Menggagas Pembatasan Dipilihnya Kembali DPR, DPD, Dan DPRD di Indonesia - Fitriyani, Desi (Jurnal Konstitusi & Demokrasi, 2023)
The term of office of the DPR, DPD, and DPRD has not been limited to the possibility of re-election. This means that those who have served have the opportunity to continue to serve for life as long as they are re-elected through elections. This tenure arrangement has also been brought to the Constitutional Court several times because it is considered contrary to the constitutional rights of citizens. However, it has never been granted by the Constitutional Court. The purpose of this research is to find an ideal idea related to the limitation of the possibility of re-election of members of the DPR, DPD, and DPRD in Indonesia. The type of research used is doctrinal legal research. The results show that the limitation of the possibility of re-election of members of the DPR, DPD, and DPRD has its own advantages and disadvantages. For this reason, it is necessary to limit the possibility of re-election relatively, namely 2 (two) consecutive terms of office but not too strict by opening up opportunities to re-serve as long as they have passed a 5 (five) year gap. This is to reduce the potential for abuse of power and to provide opportunities for citizens to be elected and to vote.